HUBUNGAN EKPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SERVIS BAWAH PERMAINAN BOLAVOLI SISWA PUTRA KELAS VII SMP NEGERI 023 PEKANBARU Eka - Nirmalawati, Eka; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of male students in class VII SMPN 023 Pekanbaru. Researcher discovered a weakness of volleyball under serviced. It seen when under served many balls still not over the net and the ball is not optimal, it influences phsycal fitness like arm-shoulder muscles. The purpose of this research is to see how much the correlation of arm-shoulder with ability of vollyball under service of male student in class VII SMPN 023 Pekanbaru City. Population in this research Population in this research amount 318 people, 150 male and 168 female. Based on population that is large and within the limits the researchers set the half population is used as a sample (purposive sampling). The study sample is all male students in class VII G as many as 16 people. Research instrument measure power arm muscles used two hand medicine ball put test and under serve test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is no correlation exsplosive power of arm-shoulder with ability of volleyball under service of male students in class VII SMPN 023 Pekanbaru.Key word : explosive power of arm-shoulder muscles, under service.